The Analysis of The Impact of Medical Insurance Payment Reform on Healthcare Service Utilisation in Primary Medical Institutions and Patients' Financial Burden for Diseases - Ji, Mengmeng (International Journal of Public Health and Medical Research, 2026)
Backgroud: Medical insurance Payment Mechanism Reform aims to improve the Structure of health resources Distribution Inefficiency leading To Some People A Need For Financial Strain. Since 2019, China's implementation of DRG diagnosis-reclassification system at all levels' general hospitals has gradually been expanded nationwide. To determine whether policy changes related to medical insurance payments impact health care spending at primary healthcare institutions and the living expenses of people illening across China. Taking into account various sources of information provided in the China Health Statistics Yearbook, The National Healthcare Security Administration's Statistical Bulletin, WHO Global Health Expenditure Database between 2010-2022 for exploring trends in outpatient visits rates; admission rate, average per capita medical expenses, catastrophic health expenditure incidence. Using a DID approach to evaluate the impact of the policy. After application, the growth rate of each type of outpatient and hospitalisation expenditure decreased by around 0.5 percentage points per year separately. Two months of outpatients at the first-class hospital reached about 16.8 per cent higher than that recorded in 2003. There were over 10% incidences of CHE in the rural-household group, indicating persistent disparities. As a result, payment reform to some extent enhanced service usage rates and alleviated economic pressures; Regionally there are still issues existing. Improving the capacity of primary healthcare and revising payment policies can help achieve universal healthcare.